Fat Stores and Antioxidant Capacity Affect Stopover Decisions in Three of Four Species of Migratory Passerines With Different Migration Strategies: An Experimental Approach - Cooper-Mullin, Clara; McWilliams, Scott R. (Frontiers in Ecology and Evolution, 2022)
During migratory stopovers, birds must make decisions about when and where to travel and these decisions are likely contingent on their fuel stores, food availability, and antioxidant capacity as well as seasonal changes in key environmental factors. We conducted a field experiment on an offshore stopover site (Block Island, Rhode Island: 41°130N, 71°330W) during autumn migration to test the hypothesis that birds with greater fuel stores and non-enzymatic antioxidant capacity have shorter stopovers than lean birds with low antioxidant capacity, and to determine the extent to which this depends on migration strategy. We used a 2 X 2 factorial field experiment (two levels each of available food and dietary polyphenols) with four species of songbirds kept in captivity for 3-5 days to produce experimental groups with different fuel stores and antioxidant capacity. We attached digital VHF transmitters to assess stopover duration and departure direction using automated telemetry. Non-enzymatic antioxidant capacity increased during refueling for Red-eyed Vireos (Vireo olivaceus) and Blackpoll Warblers (Setophaga striata) fed ad lib diets, and for ad lib fed Hermit Thrushes (Catharus guttatus) supplemented with polyphenols, but not for Yellow-rumped Warblers (Setophaga coronata coronata). Glutathione peroxidase decreased during captivity and was influenced by dietary treatment only in Red-eyed Vireos. Oxidative damage decreased during captivity for all species except Yellow-rumped Warblers. Stopover duration was shorter for Vireos and Blackpolls fed ad lib as compared to those fed maintenance. Ad lib fed Hermit Thrushes supplemented with polyphenols had shorter stopovers than those fed ad lib, as did thrushes fed at maintenance and supplemented with polyphenols compared with those fed at maintenance alone. There was no influence of condition on stopover duration for Yellow-rumped Warblers. Departure direction was not strongly related to condition, and birds primarily reoriented north when departing Block Island. Thus, fat stores and oxidative status interacted to influence the time passerines spent on stopover, and condition-dependent departure decisions were related to a bird’s migration strategy. Therefore, seasonal variation in macro- and micro-nutrient resources available for refueling at stopover sites can affect body condition and antioxidant capacity and in turn influence the timing and success of migration.